Evaluation Exhaustive De La Diversité Des Plantes Aromatiques Et Médicinales De La Péninsule Tingitane (Maroc) - Ouziki, Mohamed; Taiqui, Lahcen (European Scientific Journal, ESJ, 2016)
Aromatic and Medicinal Plants (AMP) represent a large part of biodiversity. However, in the absence of a detailed record of this diversity, research and AMP development projects are generally limited to a small portion of ethnobotanical heritage. To guide prospection, exploitation and conservation studies of the existing potential, a comprehensive evaluation of the natural diversity of AMP is required. The western Rif region in northern Morocco, which area represents less than 1% of national territory, is home to about 50% of the Moroccan floristic richness (2053 species and infraspecific taxa). This heritage includes 630 taxa from which only 23 are currently exploited and merely 57% are recognized by ethno-botanists. Among these assets, a list is drawn up containing 106 taxa with a special conservation status (very rare or rare taxa, and / or endemic and / or threatened) and some of which are widely exploited. From a phytosociological point of view and based on an available database of 449 floristic samples, natural forest stands and matorrals contain about 27% of all MAP of the study area. These AMP organize almost half the floristic composition of sclerophyllous forests (oleaster, kermes oak and cork oak forest) and about a third of the richness of each of the other groups analyzed (thermophilic formations, pure fir, limestone mountains forest, calcifuges deciduous, maritime pine, matorrals). Mountain groups are the richest in exclusive, endemic, rare and endangered AMP.